Literature Review: How Family Economic Conditions, Social Factors, and Psychological Factors Influence Student Learning Performance in Indonesia - Brilla Dinar Nastiti; Resa Wanda Fania; Tetra Amaliah Jauza; Maharska Bayu Imani; Muhammad Thufail Haq (P3I UMSurabaya, 2025)
This literature review examines how family economic conditions, social factors, and psychological factors influence students’ academic performance in Indonesia. Using a Systematic Literature Review (SLR) approach, the study synthesizes findings from national journal articles published between 2015 and 2025. The results indicate that family economic status significantly affects learning achievement through the availability of learning facilities and financial stability; however, emotional and motivational support can offset economic limitations. Social factors—such as family involvement, school environment, and community support—create a positive learning atmosphere that enhances motivation and discipline. Meanwhile, psychological factors, including intrinsic motivation, emotional intelligence, self-discipline, and emotional support, play a crucial role in improving academic resilience and optimizing learning outcomes. The interaction among these three domains demonstrates that student performance is shaped by a multidimensional process that requires an integrative and holistic educational policy approach. Such policies should not only address school quality but also focus on family welfare, social empowerment, and psychological well-being to promote educational equity and excellence in Indonesia.